2006
DOI: 10.1017/s0790966700009952
|View full text |Cite
|
Sign up to set email alerts
|

Older people with enduring or recurrent severe mental illness in the Eastern Region of Ireland

Abstract: Objectives: There has been no specific planning for older people with enduring or recurrent severe mental illness in Ireland. This survey aims to identify the number of affected over 65 year olds (graduates) and 55-64 year olds (prospective graduates) in the Health Service Executive, Eastern Region, their diagnoses and their use of psychiatric services.Method: A comprehensive survey of the ten general adult psychiatry and four old age psychiatry services in the (HSE) Eastern Region was undertaken for the year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previous Irish research has highlighted the need to plan for graduates in Ireland following the closure of psychiatric institutions (Wrigley et al 2006a(Wrigley et al , 2006b. Lawlor and colleagues demonstrated that graduates in psychiatry of later life services had higher overall service utilisation than their non-graduate counterparts in the same service which highlighted the debate as to which service should care for this group of patients (Lawlor et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous Irish research has highlighted the need to plan for graduates in Ireland following the closure of psychiatric institutions (Wrigley et al 2006a(Wrigley et al , 2006b. Lawlor and colleagues demonstrated that graduates in psychiatry of later life services had higher overall service utilisation than their non-graduate counterparts in the same service which highlighted the debate as to which service should care for this group of patients (Lawlor et al 2006).…”
Section: Introductionmentioning
confidence: 99%